Design, testing and evaluation of an end-effector for self-relocation. Issue 12 (3rd July 2015) - Han, Feng; Sun, Kui; Liu, Yu; Liu, Hong
SUMMARY: Two identical end-effectors are indispensable for self-relocation of a space manipulator, which is an effective way of extending its servicing capability. The prototype design is intimately linked to the requirements. The significant features and functionality of the end-effector and its grapple fixture are described, including the key analysis efforts. The characteristics of the end-effector and their suitability for self-relocation and payload handling were confirmed by testing, which used two prototype end-effectors, a semi-physical simulation testbed system with two, six degrees of freedom (DOF) industrial robot arms, and an air-bearing testbed system with a seven DOF manipulator. The results demonstrate that the end-effector satisfies the requirements and it can work well in a simulated space environment. With the compliance motion of the manipulator, the end-effector can perform soft capture and the manipulator can securely self-relocate and handle the payload.